The Individual Agency and Social Structure Dialectic: Exploring Women’s Experiences of Remand Custody through Arts and Community-Based Research - Rutherford, Gayle; Walsh, Christine A.; Klemmensen, Meredith; Madden, Sarah (International Journal of Criminology and Sociology, 2014)
Background: Attention to the interaction between individual agency and the structural causes and solutions to repeated incarceration is important to create sustainable change. In order to create this change, we will need to work in new ways to investigate the issues and to collaboratively identify and implement solutions. Purpose: Arts-and community-based research methods were used to explore the experiences and personal knowledge of women in remand custody. Results: The findings substantiate current knowledge of the underlying causes of women’s incarceration, including both structural issues (e.g., poverty, inaccessible education and employment, housing instability) and personal issues (e.g., addictions, history of family violence). Although the women acknowledged individual responsibility, attention to the structural causes and solutions to the cycling in and out of incarceration is fundamentally important, underpinning all of the women’s recommendations. Conclusion: The challenge of reducing the cycle of repeated incarceration for women will require a concerted collaborative effort using creative endeavors that bring the knowledge and experience of the women together with key players who can influence change at both the individual and the systemic levels